SEMANTIK AL-QUR'AN : ANALISIS PENGGUNAAN KATA LIBĀS PRA DAN PASCA QUR`ANIK - Taufiqotuzzahro, Azzah Nurin (AL ITQAN: Jurnal Studi Al-Qur'an, 2016)
This study sought to analyze the use of the word libās in the Qur'an. Besides plays as concepts related to everyday life, the concept of clothing in the word libās yet fully revealed. Many thought that libāss in the Qur'an only have meaning as clothing. In fact, the word libās in the Qur'an includes of several meanings. Besides, the word libās be an interesting keyword to be studied in linguistic studies, especially using semantic analysis, hope, it can appearing the dynamic messages from The Koran vocabularies which is containing inside by examining analytically toward the concepts which seems to play an important role in the formation of Qur'anic vision. This paper concludes that the basic meaning of libās is wearing, and satara (covering). While the relational meaning that once covered later developed into an object that is used to cover (clothes). While the significance of libās from pre and post Qur`anic are same, that is covering. But in its development, The Koran refers to a new meaning as jewelry that used to adorn self (illegitimate). Comprehensively, the concept of libās from the meaning development from pre-Islam to the birth of Islam is drafted by covering something that must be covered. Indicatively, this things becomes characterizes the uniqueness of the Koran, as well as when The Koran adopts a vocabulary from pre-Islamic period which does not immediately change the meaning inside.